THE INFLUENCE OF WORK ETHIC AND ORGANIZATIONAL COMMITMENT ON THE PRODUCTIVITY OF EMPLOYEES AT THE AGAM REGENCY EDUCATION OFFICE - Putra, Doni Guswandi; Aristiawan, Dhani; Aima, M. Havidz; Fitriyeni, Fitriyeni (Gapenas Publisher, 2025)
This study aims to analyze the influence of work ethic and organizational commitment on employee productivity at the Agam Regency Education Office. The underlying problem of this study is the low motivation and loyalty of employees, which impacts work productivity. This study uses a quantitative approach with an associative research type. The population in this study amounted to 56 employees and the sampling was carried out using total sampling. Data were collected through questionnaires and analyzed using validity, reliability, normality tests, t-tests, F-tests, and coefficient of determination (R²). The results of the study indicate that, partially and simultaneously, work ethic and organizational commitment have a positive and significant effect on employee productivity. The coefficient of determination value of 73.4% indicates that the two independent variables are able to explain variations in employee productivity substantially. This finding confirms that increasing employee productivity can be achieved by strengthening work ethic and organizational commitment synergistically.